CdS-derived CdS1−xSex nanocrystals within TiO2 films for quantum dot-sensitized solar cells prepared through hydrothermal anion exchange reaction. (1st October 2020) - Deng, Jianping; Li, Le; Gou, Yuchun; Fang, Junfei; Feng, Rong; Lei, Yilong; Song, Xiaohui; Yang, Zhi
Abstract: Composition dependent band gap engineering enables the ternary CdS1-x Sex quantum dot to be a promising candidate for quantum dot solar cell (QDSCs). Up to date, using precursor containing Cd 2+, S 2− and Se 2−, the hot-injection solvothermal synthesis, the successive ion layer absorption and reaction, and the chemical bath deposition methods, have been developed to prepare the CdS1-x Sex QDs. However, it is difficult for these processes to accurately control the CdS1-x Sex QDs synthesis. Ion exchange, as a secondary transformation synthesis method, provides a new pathway to design complex nanostructures. In the present study, a series of CdS1-x Sex QD-sensitized mesoporous TiO2 films with controlled composition and light harvesting were synthesized using a hydrothermal anion exchange reaction (HAER) method. The composition stoichiometry of CdS1-x Sex QDs together with their band gaps in the range of 550–750 nm, were easily controlled by simply tuning the HAER temperature and time duration, while maintaining a similar morphology and crystal structure. Using these CdS1-x Sex QD-sensitized TiO2 films as photoanodes for solar cells, a high power conversion efficiency of 4.03% based on CdS0.75 Se0.25 QDs was achieved under simulated AM1.5 100 mW cm −2 illumination.